Aspek Penilaian dalam Perusahaan Dot Com - Rachmawati, Dyna (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
New economy has come, begun by the advancement of information technology. It appears much dot.com company. Valuing the dot.com has challenged many financial experts. It becomes uneasy because the uncertainty is so high. This paper uses two approaches in valuing the dot.com company. The first one is qualitative approach. This approach requires acquainted of the company deeply by knowing the management team and business plan. The second one is quantitative approach. It offers two alternatives method, which is net present value or discounted cashflow and economic value added. Both are requires many assumptions. This paper tries to implement the valuation by valuing Indo.com. The result shows Indo.com has o great management team. Indo.com business is real though running the cyber business. Indo.com worth S 77 million under the assumptions made and using net present value methods